PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENANGANI PERMASALAHAN EKSPLOITASI ANAK PADA PERTAMBANGAN MIKA DI INDIA - Rizka Gusnia Ananda; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Child exploitation has become a phenomenon in international society. India has become one of the highest number of child workers in the world, and one of India’s regulations stipulates that children under 14 years of age are allowed to work under restrictions that are not in harmful categories and that mining falls into harmful categories. This study will analyze the role of the international labour organization in treating the exploitation of belt-mining workers in India. The study itself covered a limited period of time from 2011-2018 and used literature analysis methods or library research. Exploitation of child labor is certainly a violation of human rights. Then the united nations forming an organization to address the the exploitation of child workers in the world. The role of ILO that playss in addressing the problem of child exploitation of mica mines in India can be seen from two sectors. The first is human rights enforcement. Where ILO issues a work program to enforce human rights in this regard when it receives a child’s right to education and proper treatment. The second is through humanitarian aid. ILO provides training for children who are already working in the mines as well for children who have not yet worked. Training consist of basic training for children from 5-11 years, vocational training for 11-14 years, and self-sufficiency of society for parents.              Keywords: Child Labour, Mica Mines, Role of ILO, India, Exploitation of Child Labour.